Evaluasi dan Perbaikan Antarmuka Pengguna pada Website SMAN 1 Polewali menggunakan Metode Human Centered Design dan Use Quistionnaire - Muh. Akbar Murad; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
SMAN 1 Polewali (Smansa Polewali) is one of the upper secondary education institutions that provides a website as a technology-based facility in conveying information to all components, both educators, educated, to the public. Even so, since it was held in 2011 until now there are stillproblems usability including regarding interfaces such as interface design which is considered to have too many colors, inappropriate font selection, quite complicated menu choices, excessive use of images, and writing that is considered too small. In addition, on the layout side of the website, Smansa Polewaliin this case, the submenus are considered too many, as well as the less strategic position of the images, and the disproportionate size of the buttons. This of course has an impact on the lack of user interest in accessing thewebsite Smansa Polewali, so that the vital function of the website as a forum for conveying information is not achieved. In connection with these problems, further research that the researcher has prepared to solve this problem is by using theapproach Human Centered Design and themethod USE Questionnaire, in which theapproach is Human Centered Design used to identify users and divide users into several groups, as well as conduct interviews with questions. open questions that are asked to collect problems faced by users when accessing thewebsite Smansa Polewali. While the use of questionnaires is used to measure four aspects of usability, namely usefulness, ease of use, ease of learn, and satisfaction. So that in this researchimprovements andhave been made usability , significantto thewebsite Smansa Polewali. It can be seen in the percentage value of theaspect of usabilitythewebsite Smansa Polewalibefore the research was held the average value was 54.88%, while after repairs the average value obtained reached 87.52% from the results of interviews conducted with all respondents. Recommendations for improving the usability of thewebsite Smansa Polewaliproduce a new look with the aim of increasing usability.